V. V. KALKO: UKRAINIAN ANTI-PROVERBS: CAUSES OCCURRENCE - KALKO, V. V. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Summary. Introduction. Phraseological units of a language, including proverbs and anti-proverbs, take the center stage in studying cultural peculiarities of a nation. Nowadays, the reflection of gender in languages has much gained in importance and scholars are particularly interested in anti-proverbs which can be defined as alterations of traditional paremias manifesting the changes happening in the society. The purpose of the article is a analyze the reasons for the emergence of transformed Ukrainian paremias. To achieve this goal, the author collected relevant items from dictionaries and Internet. Results. Creating parodies of traditional proverbs and their purposeful recasting is not a very new phenomenon, but the term itself is quite new. Professor of Vermont University W. Mieder has coined the term ‘anti-proverb’ for such deliberate proverb innovations. The paper offers a detailed analysis of modern Ukrainian anti-proverbs deliberated and innovative variations of traditional proverbs and sayings by changing their exterior shape and their interior form. The aim is to reject tightened sapiences of proverbs and sayings by developing humorous effects. Existing mental and cultural overused cliches become derided up to the very bottom of peoples behaviour and their all day life. That makes anti-proverbs a part of laugh culture. Attention is paid to the semantic and cognitive components, which is understood as historically formed structural and semantic modification of the proverbs showing the change in the cognitive consciousness of native speakers of the language to a particular object or phenomenon of the surrounding world because of the change in relation to it due to extralinguistic causes (social, economic, etc.). Originality. Differences between proverbs (sayings of edifying character, which contain the centuries-old experience of the people) and anti-proverbs (the authors consider anti-proverbs to be the semantic antithesis of proverbs) are highlighted. The authors pay special attention to the study of the semantics of proverbs and their transformants to identify relevant semantic and cognitive characteristics. The analysis revealed that Ukrainian anti-proverbs mostly tend to reflect political and economical issues. Dominant feature of anti-proverbs is their mocking and humorous nature where humour emerges through unexpectedness and violation of the old folk wisdom. Conclusions. Thus, it should be noted that despite the fact that the anti-proverbs are ironic and humorous in nature, they reflect gender images fixed in a culture. Anti-proverbs is the phenomenon of carnival that characterizes almost all the spheres of communication nowadays, and the linguistic means of its presentation in the modern newspaper discourse.